Determinants of tax compliance intention among Jordanian SMEs: A focus on the theory of planned behavior - Tareq Bani-Khalid; Ahmad Farhan Alshira'h; Malek Hamed Alshirah (Economies, 2022)
The present study aimed to adopt the extended theory of planned behavior (TPB) to determine the intentions of owner-managers in SMEs towards engaging in sales tax compliance. The study distributed a total of 660 questionnaire copies through systematic random sampling to the mangers/owners of Jordanian manufacturing SMEs, from which 385 questionnaire copies were retrieved and considered useable and appropriate for further analysis. The study made use of Partial-Least Squares-Structural Equation Modeling (PLS-SEM) for the validation of the measurement model and structural model, and to establish the predictive relevance of the proposed model. Based on the obtained findings, the attitude towards behavior, subjective norms, perceived behavioral control and patriotism were significant determinants of the intentions towards engaging in sales tax compliance among the examined enterprises.
Keywords: 330; attitudes; patriotism; perceived behavioral control; sales tax compliance; subjective norms